Pengaruh Model Pembelajaran Langsung Berbantuan Media Laboratorium Terhadap Kreatifitas Fisika Siswa SMA - Ria Rizki Ekasari; Gunawan Gunawan; Hairunnisyah Sahidu (Department of Physics Education, Universitas Mataram, 2016)
This research aims to investigate the influence of direct instruction model with virtual laboratory media toward student creativity in physics using